No More Rights Without Remedies - Davis, Robert C.; Anderson, James M.; Howley, Susan; Dorris, Carol; Whitman, Julie (RAND Corporation, 2023)
This report captures the scope of National Crime Victim Law Institute victims’ rights clinics and describes how clinic representation affects the exercise of rights in individual cases, the legislation, court rules, appellate decisions, and media reporting pertaining to victims’ rights before and after the start of the clinics.